Accuracy of using serum D-dimer for diagnosis of acute intestinal ischemia: A meta-analysis. Issue 13 (March 2017) - Sun, Da-Li; Li, Shu-Min; Cen, Yun-Yun; Xu, Qing-Wen; Li, Yi-Jun; Sun, Yan-Bo; Qi, Yu-xing; Lin, Yue-Ying; Yang, Ting; An, Li-Ya; Su, Kun; Li, Wei-Ming; et al.
Abstract: Objective: The purpose of this meta-analysis is to comprehensively assess the accuracy of serum D-dimer for the diagnosis of acute intestinal ischemia. Methods: Diagnostic studies of D-dimer for accurate diagnosis of acute intestinal ischemia were extracted from 6 databases, and prospective and retrospective studies that provided adequate data on sensitivity and specificity were included here. Sensitivity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were calculated. The overall diagnostic performance of D-dimer was assessed by plotting a summary receiver operating characteristic curve (SROC) and calculating the area under the curve (AUC). Results: A total of 1300 patients with suspected acute intestinal ischemia from 12 studies met the inclusion criteria. The combined sensitivity, specificity, PLR, NLR, and DOR were 0.94 (95% CI: 0.87–0.97), 0.50 (95% CI: 0.40–0.61), 1.9 (95% CI: 1.5–2.3), 0.12 (95% CI: 0.05–0.26), and 16 (95% CI: 7–39), respectively. The AUC was 0.81 (95% CI: 0.78–0.84). Conclusion: The results of this meta-analysis suggested that plasma D-dimer detection might be a useful means of identifying patients with acute intestinal ischemia of the abdomen. Abstract : Supplemental Digital Content is available in the text